Design of an Explosion Vessel for Study of Flame Propagations - A Rahman, Hamizah (Universiti teknologi petronas, 2008)
This report explains about the design of an explosion vessel in Universiti Teknologi PETRONAS (UTP). Recently, there are many researches and studies about combustion that have been established in the university. In this learning process, an explosion vessel would be a proper medium to study about the flame characteristics and the things that related to the combustion. Hence, a design of an explosion vessel will bring many benefits in UTP. The objective of this project is to design an explosion vessel that will be able to withstand the certain conditions such as maximum working temperature and pressure. The design of the prototype must be durable, reliable and in compliance with the safety regulations and standards to ensure the safe working conditions. The scope of study of this project includes on the design of an explosion vessel starting from the design, material selections, codes of standard and factor of safety. There are several steps in the methodology to design the vessel where the maximum working temperature and pressure are identified in order to calculate the vessel stresses. Suitable materials to build this prototype will be determined based on the vessel stress. The auxiliary items that will be used with the explosion vessel also been studied in order to provide the suitable and safe equipment in the experimental setup of the explosion vessel. As the project completes, technical drawings of the explosion vessel are produced. The specifications of the auxiliary items are also identified in order to ensure that the system working according to experiment requirements. In evaluating whether it is necessary to do impact testing, it is found that the test is not required based on the Minimum Metal Design Temperature (MDMT) procedure.